(untitled) (Window of Public Health Journal, 2025)
The phenomenon of menstrual disorders most often experienced by young women is dysmenorrhea, this can disturb your sense of comfort and disrupt your daily activities, generally it is not dangerous but must be treated immediately. Dysmenorrhea is caused by levels of prostaglandin and vasopressin, causing pain. Dysmenorrhea treatment can be divided into two categories, namely pharmacological and non-pharmacological. Pharmacological treatment such as taking non-steroidal anti-inflammatory drugs (NSAIDs), while non-pharmacological treatment can be done with a combination of Benson relaxation therapy and aromatherapy. The aim of this research is to determine the effect of the combination of Benson relaxation therapy and aromatherapy on the intensity of dysmenorrhea. The research design used is Quasi Experimental with a pre-experimental design, with a one group pretest-posttest design to see the effect of a combination of Benson relaxation therapy and aromatherapy before and after the intervention. The sampling technique used consecutive sampling which had been adjusted to the inclusion criteria and exclusion criteria. Data processing/statistical tests used the Wilcoxon test with a significance level of α < 0.05. The results showed a value of ρ = 0.000 where the value of ρ <α, then Ha was accepted. So it can be concluded that there is an influence of the combination of Benson relaxation therapy and aromatherapy on reducing dysmenorrhea in young women. The suggestion from this research is that this therapy can be used as an alternative therapy for those experiencing dysmenorrhea.